Extremophiles as sources of exopolysaccharides - (:unkn) unknown (Nova Science Publishers, Inc., 2011)
Extreme environments, generally characterized by atypical temperatures, pH, pressure, salinity, toxicity and radiation levels, are inhabited by various microorganisms specifically adapted to these particular conditions. These microorganisms, called extremophiles, are of significant biotechnological importance as their enzymes (extremozymes) and biopolymers possess unique properties that offer insights into their biology and evolution. The enthusiastic search for novel extremophiles has largely been stimulated by the uniqueness of their survival mechanisms. This uniqueness can be transformed into valuable applications ranging from wastewater treatment to the diagnosis of infectious and genetic diseases. One adaptation strategy of particular importance to extremophiles is the production of extracellular polymeric substances (EPSs) that envelop the cell as a barrier protecting them against environmental extremes such as desiccation, temperature, pressure, salinity, acidity, heavy metals, and radiation. Due to their many interesting physicochemical and rheological properties, these biopolymers possess novel functionality that is generally superior to petrochemicalderived polymers in aspects that embrace biodegradability, and environmental and human compatibility. Consequently, biopolymers of extremophiles are widely used in foods, cosmetics, pharmaceutical products, textiles, detergents, adhesives, oil-recovery from wells, brewing and waste treatment processes. In this chapter, we present a brief overview of life under extreme environmental conditions. This is followed by a discussion of extremophilic microorganisms and their adaptation mechanisms, and specifically focuses on the production of EPSs and their ecological and physiological functions. The application areas of industrially important EPSs from various extremophilic producer strains are also mentioned. © 2010 by Nova Science Publishers, Inc. All rights reserved.